1966
DOI: 10.1002/jcp.1040670113
|View full text |Cite
|
Sign up to set email alerts
|

The effects of modified ringer's solutions on the membrane potentials of innervated and denervated frog sartorius muscle fibers

Abstract: Comparison has been made between innervated and chronically denervated frog sartorius muscle fibers for resting potentials and a number of features of the action potential. Muscles were obtained from force-fed frogs maintained at room temperature for periods up to one year, and were studied with intracellular microelectrodes. Denervated muscles increased in sensitivity to acetylcholine by 100-400-fold. Studies were made in normal Ringer's solution, and in media in which concentrations of K+, Na+, Ca++, and C1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
1984
1984

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…2A). But, since Levine (1966) has shown that this fall does not occur when the frogs are fed, it would seem that the decrease in potentials in culture is due to inadequacy of culture conditions and not to the fact that the muscles are denervated. This is certainly so for muscles cultured for about 2 months.…”
Section: Resultsmentioning
confidence: 99%
“…2A). But, since Levine (1966) has shown that this fall does not occur when the frogs are fed, it would seem that the decrease in potentials in culture is due to inadequacy of culture conditions and not to the fact that the muscles are denervated. This is certainly so for muscles cultured for about 2 months.…”
Section: Resultsmentioning
confidence: 99%